2015
DOI: 10.1111/dote.12339
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, comparative effectiveness trial of cow's milk elimination and swallowed fluticasone for pediatric eosinophilic esophagitis

Abstract: Eosinophilic esophagitis (EoE) is a chronic, immune-mediated disease in which food antigens play a key role. Current therapeutic options are limited to long-term steroid medication and dietary elimination of multiple foods, each of which is challenging. Our objective was to compare single food elimination of cow's milk to swallowed fluticasone in pediatric EoE patients. This is a prospective, comparative effectiveness trial of newly diagnosed EoE patients (ages 2-18 years) treated with swallowed fluticasone (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 31 publications
(75 reference statements)
8
102
1
3
Order By: Relevance
“…23 We prospectively observed children treated with PPI and single food elimination of cow's milk, and we found that 64% had remission based on having esophageal count <15/hpf after 6-8 weeks of treatment. 24 In that study, successful responses to cow's milk avoidance did not relate to the presence of IgE antibodies (Unpublished data).…”
Section: Discussionmentioning
confidence: 91%
“…23 We prospectively observed children treated with PPI and single food elimination of cow's milk, and we found that 64% had remission based on having esophageal count <15/hpf after 6-8 weeks of treatment. 24 In that study, successful responses to cow's milk avoidance did not relate to the presence of IgE antibodies (Unpublished data).…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have suggested that cow's milk proteins play a major role. Indeed 60–65 % of children achieve a histological remission with avoidance of cow's milk proteins alone [27]. On the other hand, confusing results have come from assays of IgE to specific cow's milk proteins using Immuno Solid-phase Allergen Chip (ISAC) for IgE [28].…”
Section: Update On the Major Conclusion Of The Ige-reporter-mouse Stmentioning
confidence: 99%
“…It is conceivable that in some patients, as it occurs with other forms of therapy, the lack of correlation between reductions in the eosinophilic infiltration in the esophagus and symptomatic improvement after an elemental diet may be due to presence of esophageal remodeling and sub-epithelial fibrosis that may not respond to the treatment during the relatively short period of these clinical trials [97] . A more practical and acceptable treatment was conducted in a prospective trial comparing swallowed fluticasone and elimination of cow's milk [98] . After 6-8 wk, esophageal eosinophil counts decreased in 64% of patients treated with cow's milk elimination and 80% of patients treated with fluticasone.…”
Section: Treatmentmentioning
confidence: 99%
“…Cow's milk elimination also significantly improved the Mean pediatric quality of life (PedsQL) EoE Module total scores and total symptoms scores. Cow's milk elimination may be more acceptable and desirable for EoE patients who do not want to take chronic, long-term steroid medications [98] . The benefits of dietary restrictions is further supported by the reduction in the number of mast cells and its proteases since these cells seem to play a role in the pathophysiology and symptoms of EoE [99] .…”
Section: Treatmentmentioning
confidence: 99%